EXPLORING THE SPECTRUM OF HORMONAL DEFICIENCY IN PITUITARY STALK INTERRUPTION SYNDROME AND ITS OUTCOME WITH GROWTH HORMONE THERAPY: CASE SERIES FROM A TERTIARY PEDIATRIC ENDOCRINOLOGY CENTER IN MALAYSIA - Perng, Chong Chiun; Selveindran, Nalini M.; Idris, Arini Nuran; Hua, Janet Hong Yeow (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Pituitary stalk interruption syndrome (PSIS) is a rare congenital condition characterized by either isolated or combined pituitary hormone deficiency. This paper presents 6 cases of pituitary stalk interruption syndrome diagnosed and managed in a tertiary Pediatric Endocrinology Center. CASE Analytical review of the medical records of patients followed up in Putrajaya Hospital, Malaysia from year 2017–2024 revealed 6 male patients with confirmed diagnosis of PSIS. Among the cohort, 50% of them had significant perinatal events including severe neonatal jaundice, prolonged non-invasive ventilation support, sepsis or hypoxic events. A total of 17% were delivered via emergency caesarean section and the rest were born via unremarkable spontaneous vaginal delivery. Clinical presentation varied with 50% of patients presenting at birth with ambiguity of genitalia, another 50% of patients presented in adolescents with short stature and delayed puberty. Features of soft dysmorphism were observed in 67% of them. All patients have growth hormone deficiency, with 83% of them having additional pituitary hormone deficiency. Half of them have multiple pituitary hormone deficiencies. None of the patients in the cohort had clinical manifestations of diabetes insipidus. MRI imaging revealed absence of pituitary stalk on all patients. All patients who have been treated with growth hormone therapy showed improvement in height velocity with a mean of 10 (± 2.5) cm per year. CONCLUSION Children with PSIS often have a very broad spectrum of clinical and biochemical presentations. Screening and evaluation of the pituitary-hypothalamic hormone axis is critical to guide management. This clinical entity often presents with growth retardation and thus early diagnosis is critical to allow for timely management of these patients with growth hormone therapy.